Non-Pharmacological Interventions for Schizophrenia: How Much Can Be Achieved and How? - Christina Andreou; Steffen Moritz (Frontiers Media SA, 2017)
The introduction of antipsychotic agents in the 1950$1 (Bs substantially improved the treatment of schizophrenia and other psychotic disorders. However, clinical and functional outcomes are still far less than optimal for patients, and have not improved in recent years despite the development of several new antipsychotics. Efficacy rates are further compromised by medication non-adherence, which has been reported to affect more than half of patients. In response to these issues, several non-pharmacological interventions have been developed for the treatment of schizophrenia, such as cognitive behavioral therapy, cognitive remediation, social cognition training and metacognitive approaches. Although these interventions have produced promising results, there is still much controversy regarding their usefulness and applicability in clinical practice. A major impeding factor for their dissemination is possibly a lack of sufficient evidence regarding their specific indications, mechanisms of action, adverse effects, but also practical issues concerning the interpretability of respective clinical studies, such as the choice of outcome variables and control of confounding factors. The present Research Topic includes original research articles and reviews addressing these issues.s
English
Keywords: Treatment; neurocognition; Delusions; metacognition; Schizophrenia; Psychotherapy; psychosis